Introduction and analysis of optimal routing algorithm in Benes networks - Karimi, Abbas; Aghakhani, Kiarash; Manavi, Seyed Ehsan; Zarafshan, Faraneh; Syed Mohamed, Syed Abdul Rahman Al-Haddad (Elsevier, 2014)
In a total grouping of dynamic interconnection networks, safe and quick routing is so important. The Benes network is one of the dynamic interconnection networks that are good for telephone networks, multi-processor systems, parallel computers, ATM switches and Navigation and radio communication between robots. In this paper, two models of Benes routing algorithm is introduced then compare them with looping; Hassan-José and fast algorithms in the speed of running time and implementation then introduce the optimum algorithm.